Phosphine‐Catalyzed Asymmetric Umpolung Addition of Trifluoromethyl Ketimines to Morita–Baylis–Hillman Carbonates. (6th October 2016) - Chen, Peng; Yue, Zhenting; Zhang, Junyou; Lv, Xi; Wang, Lei; Zhang, Junliang
Abstract: A novel phosphine‐catalyzed, highly enantioselective umpolung addition of trifluoromethyl ketimines to Morita–Baylis–Hillman carbonates was developed and it provides facile access to optically active trifluoromethyl amines with a chiral tertiary stereocenter under mild reaction conditions. The salient features of this reaction include general substrate scope, mild reaction conditions, good yields, high enantioselectivity, ease of scale‐up to gram scale, and further transformations of the products.